United States-Iran Relations: Security Implications for Armenia and Beyond - Yepremyan, Tigran (YSU Journal of International Affairs, 2022)
This study is a comparative analysis of the United States - Iran relations and the resultant security and geo-economic implications on Armenia and beyond. It deals with the fundamentals of regional security and geopolitical and economic imperatives of the United States, Iran, and Armenia. Notwithstanding a solid rationale for mutually beneficial economic and political partnership, the Iranian nuclear issue and the relations of enmity between the United States and Iran have generated mutual mistrust making the reconciliation initiatives difficult. Hence, the paper takes into consideration the Joint Comprehensive Plan of Action (JCPOA). The normalization of the US-Iran relations will fundamentally transform the regional security architecture. The issue is of crucial relevance for Armenia. The paper utilizes the materialist and constructivist framework of the Copenhagen School of Security Studies, par excellence the Regional Security Complex Theory (RSCT), to contextualize both the geostrategic ideas and practices. The empirical starting point for this study is the fact that Iran – with its vast energy reserves, huge export potential, and key geopolitical location in Eurasia – has the potential to become a regional stabilizer and significantly diminish the geopolitical and geo-economic challenges of the wider region opening a myriad of opportunities for Armenia as a transit route to Europe. Effectively this can happen with the US-Iran rapprochement. This comprehensive perspective allows us better understand the structure of regional security and prospects of stability vis-à-vis grand geopolitical designs.
Keywords: United States; Iran; Armenia; geopolitics; regional security; RSCT theory; South Caucasus, Georgia, Azerbaijan, Turkey, trilateral cooperation, transport